WCrY smart alloys as advanced plasma-facing materials – Exposure to steady-state pure deuterium plasmas in PSI-2. (May 2018) - Schmitz, J.; Litnovsky, A.; Klein, F.; Wegener, T.; Tan, X.Y.; Rasinski, M.; Mutzke, A.; Hansen, P.; Kreter, A.; Pospieszczyk, A.; Möller, S.; Coenen, J.W.; et al.
Highlights: First plasma exposure of advanced WCrY Smart Alloys in PSI-2. 220 eV ion energy: Cr-diffusion is significant due to preferential sputtering. Influence of diffusion on erosion is modelled using SDTrimSP. 120 eV ion energy: W enrichment results in similar erosion yields for WCrY and W. Acceptable plasma performance without significant impact on oxidation. Abstract: In this paper the impact of steady state pure D plasma on WCrY smart alloys at ion energies of 120 and 220 eV is reported. For this purpose a comparison with simultaneously exposed pure W samples is drawn. Different analysis techniques employed for pre- and post-plasma sample analysis hint at a significant depletion of Cr and enrichment of W for lower ion energies. Preferential sputtering leads to enhanced volumetric loss at 220 eV. Analysis of redeposited material indicated local redeposition of Cr. Modelling the ion irradiation with SDTrimSP is used to further interpret experimental results. Depending on the sample temperature during plasma exposure and the magnitude of the ion flux, diffusion of Cr towards the surface is a determining factor for erosion of smart alloys for higher ion energies.